Strategi Komunikasi Pemasaran Terpadu (IMC) EMINA dalam Meningkatkan Brand Awareness pada Remaja di Kota Denpasar - Juarez, Ayu Made Bianca; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2022)
EMINA Cosmetics is a beauty product brand that was established in 2014. The goal of this research is to describe the integrated marketing communication that have been applied by EMINA Cosmetics in order to increase it’s brand awarness to teenage girl in Denpasar City by using qualitative approach accompanied by a descriptive method. Unit of analysis used in this research is integrated marketing communication EMINA Cosmetics in Denpasar City. The technique of determining informants is by purposive sampling technique and the selected informants are promoters and beauty advisor. Data obtained through observation, interviews and documentation. The result of this research is EMINA Cosmetics in Denpasar City’s IMC are by using a combination of several types of promotions.EMINA Cosmetics in increasing brand awareness uses the concept of a marketing mix, as well promotional mix. The type of promotion that is most powerful from other areas is interactive marketing and sales promotion.